'Good personhood' in Kosovo: a Serbian perspective from below. (2nd October 2021) - Trupia, Francesco
ABSTRACT: This research paper investigates the everyday experiences, perceptions and practices of ordinary Serb citizen outside the cluster of majority Serb villages and cities in Northern Kosovo. Through employing an emic perspective, it explores their quotidian social reality in which Serbian identity is negotiated and made meaningful. Through a focus on the everyday understanding of 'good personhood', the main aim of this research paper is to disentangle local values and uses of 'being a(good) Serb' from the externally imposed post-war discourse in Kosovo. The results of this research paper advocate are thinking of the role of Serbian communities in Kosovo and reveal that a newly pragmatic form of performing the Serbian identity has been inconspicuously emerging in Kosovo, challenging earlier assumptions of a purportedly homogenous ethno-nationalist identification preference.